1998
DOI: 10.1001/archinte.158.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Heart Disease Risk Factors to Exercise Quantity and Intensity

Abstract: Exercising more intensely could improve coronary heart disease risk factor level beyond that achieved by exercise amount alone; however, proof of causality remains to be determined from clinical trials. Exercise intensity and amounts may target specific coronary heart disease risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 71 publications
4
44
0
2
Order By: Relevance
“…6,7 The ideal amount of exercise needed to maintain fitness and reduce mortality from cardiovascular disease remains a matter of debate. [21][22][23][24][25][26] For example, Lee et al showed that moderateintensity exercise training was sufficient to generate substantial benefits, 23 and similar results have been reported elsewhere, 24,26 while Williams argued that high-intensity training produced proportionally greater effects, 22 which agrees well with a 20-year study regarding the reduction of premature mortality by high physical activity. 25 Therefore, to help clinicians and researchers to evaluate and optimize the effects of exercise, it is clear that there is a need for a simple remote, reliable, and low-cost technique, ideally one that does not require a dedicated illumination source.…”
Section: Discussionsupporting
confidence: 68%
“…6,7 The ideal amount of exercise needed to maintain fitness and reduce mortality from cardiovascular disease remains a matter of debate. [21][22][23][24][25][26] For example, Lee et al showed that moderateintensity exercise training was sufficient to generate substantial benefits, 23 and similar results have been reported elsewhere, 24,26 while Williams argued that high-intensity training produced proportionally greater effects, 22 which agrees well with a 20-year study regarding the reduction of premature mortality by high physical activity. 25 Therefore, to help clinicians and researchers to evaluate and optimize the effects of exercise, it is clear that there is a need for a simple remote, reliable, and low-cost technique, ideally one that does not require a dedicated illumination source.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, Lee et al showed that moderate-intensity exercise training was sufficient to produce substantial benefits, 24 while Williams argued that high-intensity training produced proportionally greater effects. 25 Developing a remote and reliable technique might help clinical professionals and biomedical researchers to evaluate and optimize the effects of exercise. In the present study, two different exercise levels, which represent moderate-and high-intensity exercise, respectively, were performed by 12 normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lee and colleagues showed that moderate-intensity exercise training was sufficient to produce substantial benefits 16 , while Williams argued that high-intensity training produced proportionally greater effects 17 . In the present study, two different exercise levels, which represent moderate-and high-intensity exercise respectively, were performed by 12 normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%